Preoperative embolization of meningiomas: Single center - Yildiz, Bulent; Soylemez, Burcak (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the contribution of polyvinyl alcohol particle embolization to meningioma surgery. Materials and Methods: The study included 24 patients (19 women, 5 men) who were operated for meningioma at our institution between October 2018 and October 2019. Ten patients underwent tumor embolization with polyvinyl alcohol particles before meningioma surgery, while the other 14 patients were operated directly without embolization. Groups were constituted as with embolized and non-embolized before surgery.Patient and tumor characteristics, embolization procedure, operative blood loss, operative time, and complications were compared between patients with and without preoperative embolization. Results: The patients ranged in age between 28 and 79 years, with a mean age of 54.16±10.50. Mean operative time was 4.59 hours for the embolized patients and 4.72 hours for the non-embolized patients (p>0.05). Mean hemoglobin values were decreased by 1.25g/dl in the embolized patients and 1.35 g/dl in the non-embolized patients (p>0.05). Conclusion: There were no significant differences in operative time, intraoperative blood loss, or change in hemoglobin level between meningioma patients who underwent preoperative embolization with polyvinyl alcohol particles and those who did not.